Курганная группа «Спутник» у с. Ближний Хутор на левобережье Нижнего Днестра - Синика, В.С.; Разумов, С.Н.; Лысенко, С.Д.; Тельнов, Н.П. (Материалы по археологии Северного Причерноморья, 2015)
In 2014, the employees of scientific laboratory «Archaeology» of the Tiraspol State University conducted rescue excavations of the barrows of the «Sputnik» group near village Blijniy Hutor, Slobodzeya district, on the left bank of the Lower Dniester. Barrow № 3 initiated the formation of the group. It was constructed in the Early Bronze Age above the main children's burial № 1 of the Yamnaya cultural-historical community. In the burial two temple pendants in one and a half turnover (silver and copper) were found. Obviously, one secondary burial with handmade jar vessel belongs to Babino cultural circle. Three completely robbed graves, apparently, were sunk in the mound in the Late Bronze Age. Barrows № 2 and № 4 were erected in the Scythian time; each of them contained a completely robbed burial. A rare type of burial’s overlap was fixed in barrow 2 – a wooden heptagonal cage. Handworked stone slab and fragments of Sinopean amphora as a part of commemorative feast were found in the barrow 4. The date of construction of the both barrows is IVth c. BC. Sarmatian barrow № 1, which contained a burial made in the pit of the big sizes, was the later in the «Sputnik» group of the barrows. Despite the robbery, in the burial enough impressive inventory has remained. Transport ware from the complex is represented by fragments of Roman amphorae and tableware – by the gray-clay three-handle bowl. Tools are presented by fragments of iron knives, handmade spindle whorl, and a fragment of an abrasive from sandstone and lissoir made from Thracian potsherd; cult objects – by two handmade incense cups and limestone slab. Among toiletries were found clay «pyxis» and details of the wooden box; among costume accessories – silver buckle (if it was a belt one), golden appliques and golden foil strips, as well as beads of glass paste, amber, jet-stone, nacre, bone/horn. The date of construction of the barrows № 1 could be estimated as 2nd half of 2nd c. AD.